Sufistic Approach Strategies in Enhancing Religious Moderation - Mutmainah, Mutmainah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Religious life in Indonesia is inherently diverse in terms of religion, culture, customs, and societal values. This study aims, first, to analyze the Sufistic approach strategies in enhancing religious moderation among students of STAI Syaichona Moh Cholil Bangkalan, and second, to examine the obstacles and solutions in improving religious moderation among these students. Consequently, this research is expected to contribute to strengthening religious moderation at STAIS. This study employs a qualitative research method with a phenomenological approach. Data collection techniques include in-depth interviews, observations, and documentation. Data analysis consists of data reduction, data display, and conclusion drawing, while data validity is verified through triangulation. The research findings include: first, the implementation of Sufistic approach strategies in enhancing religious moderation among STAIS students, enabling them to apply these principles in daily life despite the factual presence of differences in their environment. Strategic efforts involve accepting diversity with sincerity and openness through curriculum integration, learning methods, habituation, training, and studies. Second, the obstacles to implementing the Sufistic approach in enhancing religious moderation include: (1) the curriculum is not yet integrated with religious moderation, (2) there is no specific course on religious moderation, and (3) limited studies on religious moderation. The proposed solutions include: (1) integrating the curriculum with efforts to enhance religious moderation, (2) promoting literacy on religious moderation, (3) increasing the intensity of studies on religious moderation, and (4) incorporating local wisdom to strengthen religious moderation.